Barriers to Effective Seismic Risk Assessment in High-Rise Structures - Amera Al Aouth Hamed (المجلة الأفروآسيوية للبحث العلمي, 2024)
This article emphasizes the essential need for assessing the seismic performance of tall buildings in an increasingly urbanized and seismically active environment. Despite considerable progress in understanding and addressing seismic risks, challenges and limitations remain in accurately predicting the performance of structures under real-world conditions. Continuous research and innovation are crucial for developing more effective evaluation methods and design practices. By adopting emerging technologies, improving existing models, and fostering collaboration among stakeholders, the field can significantly enhance the resilience of tall buildings to seismic threats. Ultimately, a proactive approach to seismic performance evaluation is vital for ensuring the safety and sustainability of our built environments, safeguarding lives and property against natural disasters.